Business Strategies for PT Katalis Infra Indonesia to Expand Its Loan Portfolio in the Electric Vehicle Infrastructure Sector - Mulijadi, Erick; Putro, Utomo Sarjono (Integrasi Sains Media, 2025)
Indonesia has decided to achieve net-zero emissions by 2060, where electric vehicle (EV) adoption plays a critical role. PT Katalis Infra Indonesia (KII) – a pseudonym for a state-owned enterprise company that finances infrastructure projects in Indonesia – was given a mandate by the government to expand its operations to finance the EV infrastructure sector, comprising EV battery manufacturing plants and EV charging stations. Despite the recent mandate expansion, the company is struggling to finance a project related to this new sector. This study focuses on formulating business strategies for KII to expand its loan portfolio in the EV infrastructure sector. The study uses a qualitative method approach, starting from a literature review, benchmarking, document analysis, and semi-structured interviews with several key participants from internal and external stakeholders. The gathered data is analyzed with internal and external analysis, using several tools such as Resource-Based View (RBV) for internal analysis, Porter's Five Forces for external analysis, SWOT and TOWS matrix for strategy formulation, and gap analysis to evaluate the alignment of company capabilities with industry key success factors. The findings reveal several critical gaps with industry best practices and expectations, starting from the company's condition, which lacks technical expertise and specific credit evaluation tools in the EV infrastructure sector, limited green finance products in the new sector, and mandate expansion that does not cover key segments of the EV ecosystem. The strategy is formulated using the TOWS matrix, where each of the proposed strategies is linked with the identified gap of the company's capability and key success factors in the industry. The study concludes with an implementation roadmap and recommendations for KII regarding the key actionable solutions in implementing the strategies.